Martyrs, Relics, and Bishops: Representations of the City in Dalmatian Translation Legends - Vedriš, Trpimir (2006)
Analysing a group of Dalmatian translation legends, the author traces the "image" of the city in these accounts and addresses the problems connected with the usage of these narratives for inquiries into early medieval urban history. The Translationes, a hybrid hagiographic sub-genre connecting the hagiographic Vitae and historically more reliable forms such chronicles, were often disregarded in historiography as sources of low historical value. Besides the notorious "unreliability" of the genre, neglect of these texts was equally due to inadequate approaches to their reading. Although these documents indeed contain little "historical" data, they are nevertheless a precious source for the investigation of medieval urban identities. Tracing the chosen narrative elements and the structure of the legends, the author aims at detecting the conceptual patterns, such as the image of the city as an expression of the significance of the translations of the relics and their relation to the urban communities’ past. The texts analysed in this paper are accounts of the early medieval translations of the relics of Sts. Anastasia and Chrysogonus to Zadar, of Sts. Domnius and Anastasius to Split, and of St. Euphemia to Rovinj.
Projekt MZOS
ENG